What Is the Most Reliable Method of Measuring Glenoid Bone Loss in Anterior Glenohumeral Instability? A Cadaveric Study Comparing Different Measurement Techniques for Glenoid Bone Loss. Issue 13 (November 2021) - Arenas-Miquelez, Antonio; Dabirrahmani, Danè; Sharma, Gaurav; Graham, Petra L.; Appleyard, Richard; Bokor, Desmond J.; Read, John W.; Piper, Kalman; Raniga, Sumit
Background: Preoperative quantification of bone loss has a significant effect on surgical decision making and patient outcomes. Various measurement techniques for calculating glenoid bone loss have been proposed in the literature. To date, no studies have directly compared measurement techniques to determine which technique, if any, is the most reliable. Purpose/Hypothesis: To identify the most consistent and accurate techniques for measuring glenoid bone loss in anterior glenohumeral instability. Our hypothesis was that linear measurement techniques would have lower consistency and accuracy than surface area and statistical shape model–based measurement techniques. Study Design: Controlled laboratory study. Methods: In 6 fresh-frozen human shoulders, 3 incremental bone defects were sequentially created resulting in a total of 18 glenoid bone defect samples. Analysis was conducted using 2D and 3D computed tomography (CT) en face images. A total of 6 observers (3 experienced and 3 with less experience) measured the bone defect of all samples with Horos imaging software using 5 common methods. The methods included 2 linear techniques (Shaha, Griffith), 2 surface techniques (Barchilon, PICO), and 1 statistical shape model formula (Giles). Intraclass correlation (ICC) using a consistency model was used to determine consistency between observers for each of the measurement methods. Paired t tests were used to calculate the accuracy of each measurement technique relative to physical measurement. Results: For the more experienced observers, all methods indicated good consistency (ICC > 0.75; range, 0.75-0.88), except the Shaha method, which indicated moderate consistency (0.65 < ICC < 0.75; range, 0.65-0.74). Estimated consistency among the experienced observers was better for 2D than 3D images, although the differences were not significant (intervals contained 0). For less experienced observers, the Giles method in 2D had the highest estimated consistency (ICC, 0.88; 95% CI, 0.76-0.95), although Giles, Barchilon, Griffith, and PICO methods were not statistically different. Among less experienced observers, the 2D images using Barchilon and Giles methods had significantly higher consistency than the 3D images. Regarding accuracy, most of the methods statistically overestimated the actual physical measurements by a small amount (mean within 5%). The smallest bias was observed for the 2D Barchilon measurements, and the largest differences were observed for Giles and Griffith methods for both observer types. Conclusion: Glenoid bone loss calculation presents variability depending on the measurement technique, with different consistencies and accuracies. We recommend use of the Barchilon method by surgeons who frequently measure glenoid bone loss, because this method presents the best combined consistency and accuracy. However, for surgeons who measure glenoid bone loss occasionally, the most consistent method is the Giles method, although an adjustment for the overestimation bias may be required. Clinical Relevance: The Barchilon method for measuring bone loss has the best combined consistency and accuracy for surgeons who frequently measure bone loss.